MOBERAK (Motor Bebas Bahan Bakar Ramah Lingkungan) - Rahmat Nur Madani; Raeka Widi Anggeraeni; Dinar Mutia; Dasmo Dasmo; Ahmad Jahrudin (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2020)
The vehicle is an important requirement for daily activities. The increasing number of vehicles in Indonesia from year to year correlates with the worsening air quality, especially in big cities like Jakarta. Data also shows that 70% of air pollution in Jakarta comes from motorized vehicles that use fossil fuels. One source of energy that can be an alternative solution is electric-powered vehicles because they have advantages, which are not producing pollution. Electric vehicles generally use lithium batteries as a source of electric power. Lithium batteries that have been used up are generally just thrown away without going through the processing so that they will contaminate water and soil. Therefore, we want to make vehicles that are not dependent on fossil fuels, produce no pollution, and can do auto charging electric so they don't rely on PLN electricity. This vehicle can charge independently because it has an electromagnetic coil on the rear wheel that will produce GGL induction from the wheel rotation when the bike is moving. We call this vehicle MOBERAK (Environmentally Friendly Fuel-Free Motorbike).